Acute upper airway obstruction by a hairy polyp in an infant - Pazdro-Zastawny, Katarzyna; Morawska-Kochman, Monika; Dorobisz, Karolina; Gajdzis, Paweł; Kołtowska, Anna; Zatoński, Tomasz (Pediatria Polska - Polish Journal of Paediatrics, 2022)
A respiratory distress in the newborn is a severe, life-threatening emergency. Hairy polyp (HP) is an uncommon developmental lesion. It develops because of anomalies in 2 germinal layers. The aim of this paper is the presentation of a newborn girl with an acute respiratory distress in the course of a HP located in the left soft palatal wall. The lesion was successfully removed. HP of the oropharyngeal region must be included as a differential diagnosis of acute respiratory distress in infants. A transoral surgical approach allows successful and minimally invasive excision even in a newborn. Diagnostic imaging is essential to outline the HP site of origin, which can simplify surgical treatment.